The Effect of Auditor Quality on the Follow-Up of Audit Recommendation - Setyaningrum, Dyah; Gani, Lindawati; Martani, Dwi; Kuntadi, Cris (International Research Journal of Business Studies, 2013)
The purpose of this study is to measure auditor quality of The Audit Board of the Republic of Indonesia (BPK) and investigates the effect of auditor quality on the follow-up of audit recommendation. This study uses sample of local government financial statements in Indonesia from 2010-2012. Using principle component analysis method, the result shows that there are four components extracted that form auditor quality which is experience, training, motivation, and education. All four components are then combined into a single auditor quality index that represents comprehensive measure of auditor quality. The test result shows positive effect between auditor quality and follow-up of audit recommendation. This indicates that high quality auditor is able to produce appropriate recommendations that can be easily followed up by the auditee. The more recommendations are acted upon, the better the quality of local government financial statements.